The Application of Artificial Intelligence in Civil Trials: Mechanism Vs. Humanism - Tampubolon, Yunto Safarillo Hamonangan; Murwadji, Tarsisius; ., Sudaryat (Journal of Ecohumanism, 2025)
The Pillar Theory of Law posits that the core of law is divided into two pillars: logic and morality, with justice acting as a pendulum that swings between them. The pendulum comes to rest when a balance between logic and morality is achieved. Thus, justice is realized when there is stability between logic and morality, as justice is inherently dynamic and functional. Artificial Intelligence (AI) is an output of logic, while ethics is an output of morality. Philosophers universally agree that the law must evolve in line with societal advancements, particularly in the realms of digital technology and the internet. The author concludes that in civil cases, a clear distinction should be made between administrative aspects and those that fall within the judge’s authority to decide. Administrative aspects of a case can be fully delegated to Artificial Intelligence, enabling swift resolution and achieving efficiency and effectiveness. However, in matters requiring judicial discretion, AI is unsuitable. Judges must adopt a persuasive and conciliatory approach to foster reconciliation, which represents the highest form of justice in resolving civil disputes.